WELDING COPPER - ALUMINUM COMPLEX - Rosario Francia, Samuel (1998)
The bronzes - aluminum, are a major group of copper alloys in which the main alloying element is aluminum up to 14% if other alloying elements are introduced in significant percentages such as nickel, iron, manganese, silicon acquire properties physical, mechanical or chemical of great magnitude and meets a variety of requirements engineering. There are four major groups of aluminum bronzes.